Disturbance of normal cell cycle progression enhances the establishment of transcriptional silencing in Saccharomyces cerevisiae. - Laman, H (1995)
Previous studies have indicated that mutation of RAP1 (rap1s) or of the HMR-E silencer ARS consensus element leads to metastable repression of HMR. A number of extragenic suppressor mutations (sds, suppressors of defective silencing) that increase the fraction of repressed cells in rap1s hmr delta A strains have been identified. Here we report the cloning of three SDS genes. SDS11 is identical to SWI6, a transcriptional regulator of genes required for DNA replication and of cyclin genes. SDS12 is identical to RNR1, which encodes a subunit of ribonucleotide reductase. SDS15 is identical to CIN8, whose product is required for spindle formation. We propose that mutations in these genes improve the establishment of silencing by interfering with normal cell cycle progression. In support of this idea, we show that exposure to hydroxyurea, which increases the length of S phase, also restores silencing in rap1s hmr delta A strains. Mutations in different cyclin genes (CLN3, CLB5, and CLB2) and two cell cycle transcriptional regulators (SWI4 and MBP1) also suppress the silencing defect at HMR. The effect of these cell cycle regulators is not specific to the rap1s or hmr delta A mutation, since swi6, swi4, and clb5 mutations also suppress mutations in SIR1, another gene implicated in the establishment of silencing. Several mutations also improve the efficiency of telomeric silencing in wild-type strains, further demonstrating that disturbance of the cell cycle has a general effect on position effect repression in Saccharomyces cerevisiae. We suggest several possible models to explain this phenomenon.